Organic matter content from sediment cores of coastal vegetated ecosystems in Colombia, Germany and Malaysia using stepwise loss on ignition - Theresa-Marie Fett; Jennifer Prugger; A Aldrie Amir; Robin Aßmann; Hannah Delventhal; Feenja Domanski; Delfina Ernst; Hamia Sophia Fatima; Emilia Fernes; Mondane Fouqueray; Jana K Geuer; Clarisse Gösele; et al. (PANGAEA, 2025)
This dataset contains measurements of the top 50cm of sediment collected between 2021 and 2023 as part of the project sea4soCiety. Sampling took place in three locations each on the North Sea and Baltic Sea coast of Germany, the coasts of peninsular Malaysia and the Caribbean coast of Colombia. To quantify the storage capacity of blue carbon in coastal vegetated ecosystems (mangrove forests, saltmarsh, and seagrass meadows) and unvegetated marine sediments in each location and ecosystem five to nine 50 cm deep sediment cores were collected using a peat sampler (5.2 cm diameter, 50 cm length, Royal Eijkelkamp). Sediment cores were split visually according to visible physicochemical layers and each layer was thoroughly homogenized. Sub-samples for organic matter analyses were frozen at -20°C prior to freeze-drying. Freeze-dried material was pulverized with a ball mill (LLC Planetary Micro Mill PULVERISETTE 7 premium line, FRITSCH) at 500 rpm for 3 min. To determine the organic matter content (containing organic carbon) 3 g freeze-dried and pulverized sediment was stepwise combusted for 4h at 180°C, 300°C, 400°C and 500°C in a muffle oven (M110, Heraeus).